Magnetic resonance imaging characteristics of atlanto-axial subluxation in 42 dogs: Analysis of joint cavity size, subluxation distance, and craniocervical junction anomalies - Kathryn Y. Bray; Simon R. Platt; Marc Kent; Natasha J. Olby; Peter J. Early; Christopher L. Mariani; Karen R. Muñana; Shannon P. Holmes (Open Veterinary Journal, 2023)
Background: Atlanto-axial (AA) subluxation can be a complex syndrome in dogs. Accurate identification and assessment of this condition is key to providing treatment and resolution. Aim: The purpose of this retrospective study was to describe the magnetic resonance imaging (MRI) characteristics of AA subluxation and associated neurologic deficits. Methods: A multicenter review of dogs with a diagnosis of AA subluxation was conducted, evaluating signalment, neurologic grade, duration of signs, and MRI characteristics. MRI characteristics included degree of spinal cord compression and joint subluxation, integrity of odontoid ligaments, presence of a dens, spinal cord signal intensity, and presence of syringohydromyelia, hydrocephalus, and Chiari-like malformation. A control population with normal AA joints was also evaluated. MR images of 42 dogs with AA subluxation were compared to 26 age and breed-matched control dogs. Results: Affected dogs had a median age of 27 months and median weight of 2.7 kg, and the most commonly affected breed was Yorkshire terrier (47.5%). Spinal cord signal hyperintensity, increased AA joint size, and cross-sectional cord compression at the level of the dens and mid-body C2 were associated with AA subluxation. No associations were found between cord compression, appearance of the dens, or cord signal intensity and neurologic grade. Affected dogs did not have a higher incidence of Chiari-like malformation, syringohydromyelia, or hydrocephalus than control dogs, and their neurologic grade was not associated with MRI findings. Lack of a dens and/or odontoid ligaments was associated with larger subluxations. Conclusion: Dogs with clinical signs of AA subluxation were significantly more likely to have intramedullary hyperintensity at the level of compression (p=0.0004), an increased AA joint cavity size (p=0.0005), and increased spinal cord compression at the level of dens and mid-body C2 (p=1.4mm and a subluxation distance >2.5mm as cutoffs for MRI diagnosis of AA subluxation in dogs. No differences were noted between dogs with AA subluxation and control dogs regarding syringohydromyelia, hydrocephalus, and Chiari-like malformation. [Open Vet J 2023; 13(9.000): 1091-1098]